Dynamics of soft tissue thickness in the area of one-stage dental implantation with the use of a soft tissue cuff reinforced with bone graft material - Ye. Yu. Niezhentsev; S. O. Chertov (Zaporožskij Medicinskij Žurnal)
Aim. The study aims to compare the dynamics of the increase in the thickness of soft tissues in the area of one-stage dental implantation after the use of a xenogenic collagen matrix and a soft tissue cuff reinforced with bone graft material (BGM).